High-resolution semi-automatic mapping based on an Unmanned Aerial Vehicle (UAV) to capture geological structures - MOREIRA,JULIO A. (2021)
Abstract Due to the recent technological progress, Unmanned Aerial Vehicles (UAV), is an alternative for the high-resolution imaging of the terrestrial surface, helping map lineaments, essential structures on the stage of geological mapping. Therefore, this research aims to accomplish and to confirm the efficiency of the use of UAV high-resolution imaging for semi-automatic lineament mapping, in a shear zone in Guaçuí/ES. Orthomosaic was created from the UAV imaging, in which the LINE algorithm was used from Geomath PCI software for the semi-automatic mapping of lineaments. In addition, a manual lineament mapping was performed on the orthomosaic for comparison purposes, and a shaded relief image was made up of Azimuth 135° and Elevation 45°, from the SRTM data, followed by manual lineament mapping for a regional vision of the studied area. On the semi-automatic and manual extraction on the orthomosaic and shaded relief image, 61.30%, 61.63%, 57.38% of the lineaments, respectively, have NW-SE direction, showing a really strong correlation. Therefore, the semi-automatic mapping is extremely effective in terms of structural trends acquisition and can provide fine-scale data for the assessment of inaccessible areas.